Blood T-cell profiling in metastatic melanoma patients as a marker for response to immune checkpoint inhibitors combined with radiotherapy. (August 2022) - Ratnayake, Gishan; Reinwald, Simone; Edwards, Jack; Wong, Nicholas; Yu, Di; Ward, Rachel; Smith, Robin; Haydon, Andrew; Au, Pei M.; van Zelm, Menno C.; Senthi, Sashendra
Highlights: Stereotactic radiotherapy leads to increased levels of PD-1 and the activation marker ICOS in CD8+ T cells. This is accompanied by a relative reduction in circulating regulatory T cells. Combination of radiotherapy and immunotherapy reduces the proportion of circulating naive T cells. A combination of higher levels of baseline CD8+ naive T cells and of CD4+ memory cells expressing the exhaustion marker TIM-3 is predictive of response to therapy. Abstract: Background: The addition of stereotactic ablative radiotherapy (SABR) to immune checkpoint inhibitors (ICIs) has the potential to significantly improve outcomes in the treatment of metastatic melanoma. We analysed peripheral blood immune cells of patients receiving combination SABR and ICI to detect the effect of treatment and identify potential biomarkers that predict outcome. Methods: 24 polymetastatic melanoma patients participated in the SABR IMPACT trial, receiving standard dose immunotherapy with anti-PD-1 and/or anti-CTLA-4 and stereotactic ablative radiotherapy to one site. Comprehensive immunophenotyping of T-cells was performed with flow cytometry on blood samples from 13 patients at baseline and following the first 4 cycles of treatment. Results: Following four cycles of immunotherapy and SABR, the proportion of naïve subsets were reduced within both the CD4 and CD8 T-cell lineages. Independently, SABR resulted in increased expression of PD-1 (p = 0.019) and ICOS (p = 0.046) on the CD8+ T-cells, accompanied by a reduction in regulatory T-cell frequencies (p = 0.048). A multivariate discriminant analysis revealed a baseline signature of lower levels of CD8+ naive T-cells and higher expression of TIM-3 on regulatory T-cells and memory T-cells better predicted response. Conclusion: The combination of immunotherapy and SABR changed the immunophenotype of blood T cells, with some shifts attributable to SABR. Importantly, we identified a T-cell signature at baseline that best predicted response. Validation of these findings in an independent cohort could confirm these as biomarkers at baseline or early during treatment, and whether these can be utilised to stratify patients for high or low intensity treatment to reduce toxicity.